2018
DOI: 10.1111/trf.15040
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and risk factors of transfusion‐associated circulatory overload: a case control study

Abstract: BACKGROUND: Transfusion-associated circulatory overload (TACO) is a growing concern in clinical practice. STUDY DESIGN AND METHODS: A case controlstudy was performed at the Nîmes University Hospital, France. TACO cases occurring after RBC transfusion reported from January 1, 2014, to May 31, 2017, were included as cases. Four controls by case were randomly selected among the other RBC recipients on the same day. RESULTS:During the study period, 60 TACO diagnoses were reported for 37,029 transfused RBCs to a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…The incidence of TACO ranges from <1% to 8% in human studies 28 . A 2018 study reported a transfusion‐related mortality rate of 5% and named TACO the leading cause of death 30 …”
Section: Acute Respiratory Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of TACO ranges from <1% to 8% in human studies 28 . A 2018 study reported a transfusion‐related mortality rate of 5% and named TACO the leading cause of death 30 …”
Section: Acute Respiratory Reactionsmentioning
confidence: 99%
“…In patients with heart failure, pulmonary edema can occur without increases in total blood volume 29 . Patients with TACO typically have a positive response to diuretic therapy 28,30,31 …”
Section: Acute Respiratory Reactionsmentioning
confidence: 99%
“…Indeed, low body weight (<46 kg) confers 8 times the risk of TACO, and it seems a cautious volume-conscious approach to blood products may be a primary way to improve outcomes. 16 One case-control study found that among patients receiving over 4 units of any blood component, TACO rates were higher among females but not males when compared to their matched controls, but height or weight were not analyzed as specific variables by sex. 17 The fact that the quantity of blood products transfused affects people of different sizes and sexes differentially has important implications, as males and females tend to, and probably should receive different amounts of blood products in resuscitation.…”
Section: Recipient Sex-related Factors In Transfusion Reactionsmentioning
confidence: 99%
“…TACO is responsible for the highest transfusion‐related mortality; however, there is less concern for this due to lower fluid resuscitation volumes and duration in combat settings . Patients who develop TACO are more likely to have comorbidities like congestive heart failure and kidney disease . Several concerns about the potential for transfusion reaction and transfusion‐transmitted diseases (TTDs) can be mitigated through regular and recommended testing.…”
Section: Introductionmentioning
confidence: 99%
“…48,49 Patients who develop TACO are more likely to have comorbidities like congestive heart failure and kidney disease. 50,51 Several concerns about the potential for transfusion reaction and transfusiontransmitted diseases (TTDs) can be mitigated through regular and recommended testing.…”
Section: Introductionmentioning
confidence: 99%